2007
DOI: 10.1121/1.2783201
|View full text |Cite
|
Sign up to set email alerts
|

Vortex sound under the influence of a piecewise porous material on an infinite rigid plane

Abstract: The vortex dynamics and the sound generation by an inviscid vortex in the presence of a finite length porous material on an otherwise rigid plane are studied numerically in the present study in an attempt to understand the sound generation near the surface of a wall lining in a lined duct. The combined effects of the effective fluid density and flow resistance inside the porous material, and the length and thickness of the porous material on the sound generation process are examined in detail. Results obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 18 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…Therefore, only the cases where the initial height of the vortex y oi is smaller than 0.5 will be considered as the vortex is stationary if y oi = 0.5 and will move further upstream if y oi Ͼ 0.5 in the absence of a mean flow with nearly constant speed and thus radiates no sound. One can also notice that many equations involved infinite summations which have to be truncated in the computation as in many previous studies ͑for instance, Lau and Tang 18 ͒. It is found that the difference of the far field pressure amplitudes for y oi = 0.2, L =2, h = 0.2, and = 3 with various R f computed with five-term summation and ten-term summation is within 1%-2%.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…Therefore, only the cases where the initial height of the vortex y oi is smaller than 0.5 will be considered as the vortex is stationary if y oi = 0.5 and will move further upstream if y oi Ͼ 0.5 in the absence of a mean flow with nearly constant speed and thus radiates no sound. One can also notice that many equations involved infinite summations which have to be truncated in the computation as in many previous studies ͑for instance, Lau and Tang 18 ͒. It is found that the difference of the far field pressure amplitudes for y oi = 0.2, L =2, h = 0.2, and = 3 with various R f computed with five-term summation and ten-term summation is within 1%-2%.…”
Section: Resultsmentioning
confidence: 53%
“…As in the previous studies of the authors, [15][16][17][18] the air density inside the duct is denoted by while the properties of the porous materials are characterized using the effective density e and the flow resistance R f inside its lattice. 19 The flow resistance is normalized by ⌫ / d 2 .…”
Section: Theoretical Developmentmentioning
confidence: 99%
See 3 more Smart Citations